Pembentukan Portofolio Optimal melalui Single Index Model pada IDX MES BUMN 17 - Annis Maulina Kusy; Heidy Puspa Alyssa (Warmadewa Economic Development Journal (WEDJ), 2025)
This study aims to construct an optimal portfolio of stocks listed in the IDX MES BUMN 17 index using the Single Index Model (SIM). Data were obtained from 15 state-owned enterprises selected through purposive sampling for the period from May 2020 to May 2025. The analysis involved calculating actual return, beta, excess return, Excess Return to Beta (ERB) ratio, and cut-off rate (C*). The results indicate that eight stocks—BRIS, ANTM, PGAS, PTBA, JRPT, TINS, ELSA, and IPCC—meet the eligibility criteria for inclusion in the optimal portfolio, as their ERB values exceed the cut-off rate. The constructed portfolio yielded a return of 2.3% and a risk level of 1.61%, outperforming the market return of 0.67% while maintaining a tolerable risk level. These findings suggest that the SIM is an effective method for developing efficient investment strategies in state-owned enterprise stocks.